Validation of the abbreviated indicators of perceived residential environment quality and neighborhood attachment in China - Mao, Yanhui; Luo, Xinyi; Guo, Shuangyang; Xie, Mei; Zhou, Jing; Huang, Rui; Zhang, Zhen (Frontiers in Public Health, 2022)
This paper focuses on people’s assessment of their residential neighborhood in the Chinese urban context, and aims to verify the factorial structure and the reliability of the abbreviated version of the instrument comprising indicators of perceived residential environment quality (PREQ) and neighborhood attachment (NA) by factor analyses. The instrument consists of 11 scales measuring the PREQ and 1 scale measuring neighborhood attachment (NA). The 11 PREQ scales include items covering four macro-evaluative dimensions of residential quality: architectural and urban planning aspects (three scales: Architectural and Town-planning Space, Organization of Accessibility and Roads, Green Areas), sociorelational aspects (one scale: People and Social Relations), functional aspects (four scales: Welfare Services, Recreational Services, Commercial Services, and Transport Services), and contextual aspects (three scales: Pace of Life, Environmental Health, Upkeep and Care). A total of 1,332 residents in Chinese urban contexts filled in a self-report questionnaire including 11 PREQ scales and 1 NA scale. The sample was randomly split half into a calibration sample and a validation sample. Results confirmed the factorial structures of the instrument including overall 11 PREQ scales and 1 NA scale, and the abbreviated instrument yielded good internal consistency. The abbreviated version of the instrument of PREQ and NA was a further important result of this study, since it allowed a more manageable and reliable instrument, which could reduce respondents’ fatigue and annoyance, and accordingly contribute to the field of urban planning and architectural design.